Corticosteroids injections versus corticosteroids with hyaluronic acid injections in rhizarthrosis: the randomised multicentre RHIZ'ART trial study protocol. Issue 1 (9th January 2019) - Cormier, Grégoire; Le Goff, Benoit; Denis, Amélie; Varin, Stéphane; Auzanneau, Lucie; Dimet, Jérôme; Le Thuaut, Aurélie
Abstract : Introduction: Osteoarthritis of the trapeziometacarpal joint affects approximately 10%–25% of women, especially those who are postmenopausal. It may result in thumb dysfunction. Among the treatments, intra-articular injections of corticosteroid (CS) and hyaluronic acid (HA) are both effective and recommended. However, clinical trials have shown that HA improves functional capacity, whereas CS only produces a decrease in pain. The synergy of these two drugs has not been evaluated. The primary goal of this study was to determine whether the association between HA and CS produce an additional decrease of more pain during thumb movement at three months postinjection, compared to the level of pain relief from CS alone. Methods and analysis: RHIZ'ART is a prospective, multicentre, comparative, randomised, controlled, double-blind trial. Patients referred to the rheumatology department for thumb rhizarthrosis will receive an injection of betamethasone with HA or placebo (serum saline) based on central randomisation and stratification by centre. Injections will be given under ultrasound guidance. The primary outcome will compare the pain Visual Analogue Scale with motion at three months for both groups using a mixed model. The expected decrease in pain intensity in the CS group is 25% and 35% in the CS with HA group. In order to achieve a 80% power for detecting this difference with α set at 5%, 73 patients are needed in each group (146 total). The main secondary outcomes are the Cochin score (hand function) and grip strength. Follow-up visits are at 1, 3, 6 and 12 months. Ethics and dissemination: The study project has been approved by the appropriate ethics committee (CPP île de France III, 2017-002298-20). In agreement with current French regulations, a signed informed written consent will be obtained from each patient. Results of the main trial and of the secondary endpoints will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT03431584 .